Dance, Ageing and Collaborative Arts-Based Research - Herron, Rachel; Bar, Rachel; Skinner, Mark (Taylor & Francis, 2023)
Dance, Ageing and Collaborative Arts-Based Research contributes a critical and comprehensive perspective on the role of the arts -specifically dance - in enhancing the lives of older people. The book focuses on the development of an innovative arts-based program for older adults and the collaborative process of exploring and understanding its impact in relation to ageing, social inclusion, and care. It offers a wide audience of readers a richer understanding of the role of the arts in ageing and life enrichment, critical contributions to theories of ageing and care, specific approaches to arts-based collaborative research, and an exploration of the impact of Sharing Dance from the perspective of older adults, artists, researchers, and community leaders. Given the interdisciplinary and collaborative nature of this book, it will be of interest across health, social science, and humanities disciplines, including gerontology, sociology, psychology, geography, nursing, social work, and performing arts. Licence line: Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.